Panic Buying, Bauran Pemasaran, Citra Merek dan Keputusan Pembelian Produk - Bonifasius Wisandono Sarsanto (Universitas Pendidikan Nasional, 2021)
Bratamed hand sanitizer product as one of many products from PT. Brataco was increasing in sales in times of COVID-19 pandemic. The research intension is to find if there is effects of panic buying, marketing mix and brand image on purchasing decision of Bratamed hand sanitizer. Population for the research are all the customers of Bratamed hand sanitizer at PT.Brataco Yogyakarta branch and using accidental sampling technique with direct questioner to collect samples. Variables used for this research are Panic Buying (X1), Marketing Mix (X2), Brand Image (X3) for.independent.variables.and.Purchasing Decisions (Y).for.dependent.variable. Multiple.linear.regression is the analysis technique which used and then processed with SPSS for Windows 19 statistic computer program. Based on data analysis and discussion about this research it leads to result that there is an effect from each aspects which is panic buying, marketing mix and brand image on purchasing decision of Bratamed hand sanitizer.